Tourism scholarship with LGBTQ+ people in criminalised contexts: A research agenda. (September 2022) - Lewis, Clifford; Prayag, Girish
Abstract: Despite numerous calls for tourism research on the LGBTQ + community beyond western developed nations, this gap remains unaddressed in a way that empowers LGBTQ + people – particularly those in places where such identities are still criminalised. Travel can play an essential role in the lives of LGBTQ + people by providing a space for identity exploration, affirmation and reinvention. Yet, the risks inherent to participants and researchers alike have impeded such research from being conducted. This paper identifies these risks and discusses theoretical and methodological approaches to elucidate and provide solutions. Finally, a research agenda is provided to guide exploration.